THE INTERTEXTUAL RELATIONS BETWEEN SULAMITA AND IRACEMA:: THE LITERARY FEMININE INFLUENCED BY THEOLOGY - de Souza Vasconcelos Silva, Michele (Revista Gênero e Interdisciplinaridade, 2021)
This essay intends through intertextual elements, to make a comparison between José de Alencar’s Iracema and the Sulamite, central character of solomom’s Song of the Songs. Therefore this work will be organizedon theoric of the concept of intertextuality found in the works of Koch and Paulino; a literary of Proença and a theological perspective from Mesquita